2015
DOI: 10.1186/s12920-015-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

High metallothionein predicts poor survival in glioblastoma multiforme

Abstract: BackgroundGlioblastoma multiforme (GBM) is the most common and aggressive malignant brain tumor. Even with vigorous surgery, radiation and chemotherapy treatment, survival rates of GBM are very poor and predictive markers for prognosis are currently lacking.MethodsWe performed whole genome expression studies of 67 fresh frozen untreated GBM tumors and validated results by 210 GBM samples’ expression data from The Cancer Genome Atlas.Results and discussionHere we show that in GBM patients, high metallothionein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Deficiency in MT generally worsens the damage caused by neurotoxic factors or trauma (Giralt et al, 2002). However, in glioblastoma multiforme patients, high levels of MT are a negative prognostic factor, probably because MT make tumors more resistant to therapy (Mehrian-Shai et al, 2015).…”
Section: Metallothioneinsmentioning
confidence: 99%
“…Deficiency in MT generally worsens the damage caused by neurotoxic factors or trauma (Giralt et al, 2002). However, in glioblastoma multiforme patients, high levels of MT are a negative prognostic factor, probably because MT make tumors more resistant to therapy (Mehrian-Shai et al, 2015).…”
Section: Metallothioneinsmentioning
confidence: 99%
“…MT2A over-expression is associated with cell proliferation in cancerous breast tissue [ 90 ], with significantly modified breast cancer risk, and cell cycle is inhibited through silencing MT2A [ 91 ]. MT2A predicts high therapeutic value in hepatocellular carcinoma [ 92 ], whereas predicts poor survival in glioblastoma multiforme [ 93 ]. MT2A might be a chemosensitive indicator in gastric cancer (GC) [ 94 ], and another study found that MT2A might play a role in suppressing tumor activity through inhibiting NF-κB and might be a prognostic biomarker and potential target for individual therapy of GC [ 95 ] ( Table 1 ).…”
Section: Mt2a and Diseasementioning
confidence: 99%
“…The cytoprotective effect of MT3 in glioma cells has been reported by others. For instance, elevated MT3 expression in U87-MG glioblastoma cells than in normal astrocytes and other glioma cell line was correlated with an inactive conformational change of p53, resulting in attenuated apoptosis 17 . Hence, MT3 may contribute to glioma survival through diverse ways including increases in autophagy flux through lysosomal acidification.…”
Section: Discussionmentioning
confidence: 98%
“…As for glioma, induced expression of MT3 as well as MT1 and MT2 following arsenic trioxide treatment on U87-MG glioblastoma cells was demonstrated 16 , which may be postulated as a potential mechanism for glioma resistance. Importantly, Mehrian-Shai et al 17 recently reported that, in glioblastoma patients, high expression of including MT3 was associated with poor patient survival whereas low MT levels corresponded to good prognosis, suggesting the prognostic implications of Mts in glioma.…”
mentioning
confidence: 99%